Constitutional Transition in a Democratic State: A Critical View of the Omnibus Law Establishing Employment Copyright Law - Rahman, Arif; Zaini, Ahmad; Hajani, Hajani; Haerudin, Rendi; Jambunanda, Ahmad Jamaludin (Journal of Law and Legal Reform, 2024)
The debate regarding Omnibus Law as the main means for structuring legal regulations in Indonesia attracted a lot of public attention when the Omnibus Law method, which was previously little known in Indonesia as a country that adheres to the Continental European legal system, was used in the preparation of draft laws (RUU). How does the constitutional transition to the establishment of an omnibus law on copyright work in a democratic country? How do we review the constitutionality of the implementation of the Omnibus Law and the copyright mechanism in the formation of statutory regulations? This research uses the concept of normative descriptive research, or what can be called normative juridical research. With this method, law is interpreted as what is written in legislation (law in a book), or law is interpreted as a legal rule, which is a standard for appropriate behavior. The Omnibus Law method practiced in the common law system is interpreted as a (new) law that regulates various kinds of regulations to simplify the various laws that are still in force. Constitutionally, the legal position of the omnibus law concept has not been regulated in the legal system or in the laws and regulations in Indonesia. Law No. 11 of 2020 concerning Job Creation, which was formed using the Omnibus method, is considered to be constitutionally contradictory because it does not have clear objectives and formulation, both in terms of the standard of formation, the systematics of its creation, and the process of changing its substance.